The domestic fauna in the south county people's council, in Santa Clara, Villa Clara, Cuba - Armiñana-García, Rafael (2024)
Domestic fauna is constituted by the species of animals that are under the control of man, and are under his protection and attention. The objective of the research was directed to determine the domestic fauna present in the houses of different inhabitants living in the Condado Sur Popular Council in the city of Santa Clara, Villa Clara, Cuba. For the development of the research, methods of information collection and methods of processing the collected information were used, such as interviews, participative observation, revision of historical-logical documents, deductive-demonstrative and statistical and mathematical methods, among which the descriptive statistical method is emphasized. A total of 300 homes were visited, and the presence of 39 vertebrate species was found, of which 13 are mammals, 24 birds, and two reptiles. Of these species 13 are endemic to the Cuban fauna, three are considered invasive exotic species and the rest are introduced. In addition, the presence of stray dogs and cats was verified.